Relasi Antara Perguruan Tinggi Desain Komunikasi Visual (DKV) di Indonesia dengan Industri DKV - Wibowo, Hastjarjo Boedi (Bina Nusantara University, 2011)
College institution of visual communication design (DKV) today is becoming the biggest creative education in design in Indonesia. The growth that will be more than 1000% since 1990 should be seen. Private college institutions are the biggest caretaker of DKV college institution in Indonesia, so it will take part in defining the colours of DKV education in Indonesia. The article begins with the definition of DKV and about its education history and the relation between DKV education, industry and profession today. The article tries to criticize proportionally the happening circumstances based on literature study, as laws, government regulations, and other references. The relations between college institution of DKV in Indonesia and the DKV industry are important synergy in creating quality human resources, which involved dependence and needs.